Comparison of the efficacy of continuous intravenous infusion versus intramuscular injection of epinephrine for initial anaphylaxis treatment. Issue 1 (20th October 2022) - Fujizuka, Kenji; Nakamura, Mitsunobu; Tamura, Junichi; Kawai‐Kowase, Keiko
Abstract : Aim: Continuous intravenous (CIV) infusion of epinephrine for the treatment of anaphylaxis may be required if symptoms do not improve after intramuscular (IM) injection. As CIV infusion permits precise dose adjustment, we compared treatment course and adverse events following CIV infusion and IM injection of epinephrine for the management of anaphylaxis. Methods: Medical records of patients, who were treated for anaphylaxis with epinephrine, were 18 years or older, and were admitted to our department from April 2005 to March 2016, were retrospectively reviewed. The cases were categorized as CIV infusion or IM injection, and treatment course and outcomes were compared between the two groups. Results: Of the 142 eligible cases, there were 78 in the CIV infusion group and 64 in the IM injection group. The CIV infusion group had lower systolic blood pressure, more respiratory symptoms, and higher Acute Physiology and Chronic Health Evaluation II (APACHE II) scores, but required a lower total dose of epinephrine, had fewer adverse events after epinephrine administration, and showed lower incidence of biphasic reactions. In addition, compared with the IM injection group, time to administration of epinephrine was significantly longer ( P  < 0.001), but time to resolution of symptoms, both from contact and epinephrine administration, was significantly shorter ( P  < 0.01 and P  = 0.03, respectively). Conclusion: Continuous intravenous infusion of epinephrine for the treatment of anaphylaxis may be safe, has fewer adverse events, improves symptoms, and is relatively easy to administer under ready conditions. CIV infusion of epinephrine may also reduce the incidence of biphasic reactions. Abstract : Our analysis shows that compared to intramuscular injection epinephrine, continuous intravenous (CIV) infusion of epinephrine for the treatment of anaphylaxis has fewer adverse events, improves symptoms, and is relatively easy to administer under ready conditions. CIV infusion of epinephrine may also reduce the incidence of biphasic reactions.